Review Juridical Element Abuse Power In Action Criminal Corruption By System Law Criminal In Indonesia - Andre Yosua M; Tegar Mulia (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Research on the concept of abuse of authority in the Corruption Constitution in Indonesia, elaborating on this problem along with the concept of abuse of authority in decisions court. Elaboration with normative research methods, in the final results show that any inconsistency in the formulation of the offense in Article 3 of the PTPK Law. The location of the inconsistency is an element from violation First with Meaning enrich self Alone, person other, or corporation formulated in a way material, whereas element 2nd can harm finance country or economy. Formal Terms Which formulated on base thinking This, that is element violation to abuse authority, chance, or means Which he has because of his position/position. The solution is possible with certain characteristics among the concept of breaking law with draft abuse authority And in practice his, proof abuse authority is matter Which difficult, Because For evaluate abuse This authority is factually related authority, suggested in Article 3 of Law no. 31 of 1999 jo. Act No 20 Year 2001 deleted just. Reason others are: element deed oppose law in Article 2 Law no. 31 of 1999 jo. UU no. 20 of 2001 has been able to accommodate the elements abuse of authority, because abuse of authority is a species of the genus element violate law.